Scoping Review: A Hybrid Delivery Model of Pain Management...2024 American Society for Pain Management Nursing (ASPMN) Annual Conference, October 16-19, 2024, San Antonio, TX. - Pervis, Brian (Pain Management Nursing, 2025)
This scoping review explores hybrid healthcare models combining telehealth and in-person visits for pain management. It examines their components, effectiveness compared to traditional care, advantages, and disadvantages of telehealth, and the influence of future technologies. The review followed the JBI scoping review methodology and used the PRISMA-ScR checklist. Studies on hybrid pain management models involving adult patients and clinicians were included. Searches were conducted in PubMed, CINAHL, and Google Scholar, along with gray literature from healthcare organizations. Studies were screened based on Population, Concept, and Context (PCC) criteria. Data extraction followed a modified JBI tool, with thematic analysis and descriptive statistical summaries of study findings. Hybrid care models combining telehealth and in-person visits improve access to pain management, particularly in rural areas, and reduce costs. Telehealth provides convenience but faces barriers such as privacy concerns, technological disparities, and patient preference for in-person visits. In-person care remains crucial for diagnostics and patient-provider trust. Future technologies like machine learning show promise for enhancing these models. Hybrid models offer a flexible, cost-effective approach to chronic pain management. While telehealth expands access, challenges include privacy issues and digital inequities. Future technologies will likely improve these models' personalization and efficiency. Nurses should be trained in telehealth technologies to facilitate the implementation of hybrid models while continuing to provide essential in-person care to engage patients and build trust.